2016
DOI: 10.3390/coatings6040048
|View full text |Cite
|
Sign up to set email alerts
|

Self-Cleaning Mineral Paint for Application in Architectural Heritage

Abstract: A mineral silicate paint has been developed for architectural heritage. To enhance durability, any type of organic additive has been avoided. Potassium silicate was the binder agent intended to give strong adherence and durability to stone and concretes. Incorporation of mainly anatase titanium dioxide was intended to act both as a white, bright pigment and as a photocatalyst. Reflectivity analyses on the paint in the visible-to-near infrared wavelength region show high solar heat reflection. The self-cleaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The contact angle of water droplets on graphene and graphene-TiO2 films are shown in Figure S5, where it is found that graphene-TiO2 film is highly wetting (small contact angle) and therefore superhydrophilic. This is due to the hydrogen bonding and strong interlinking between Ti-O and unsaturated -O and -OH groups on graphene [12,[40][41][42]. It is known that TiO2 surface is self-cleaning, meaning that it removes the surface dirt, such as organic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The contact angle of water droplets on graphene and graphene-TiO2 films are shown in Figure S5, where it is found that graphene-TiO2 film is highly wetting (small contact angle) and therefore superhydrophilic. This is due to the hydrogen bonding and strong interlinking between Ti-O and unsaturated -O and -OH groups on graphene [12,[40][41][42]. It is known that TiO2 surface is self-cleaning, meaning that it removes the surface dirt, such as organic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the protection of stone-built cultural heritage has attracted the attention of researchers in various fields. Stone-built cultural heritage exposed to weather conditions can be damaged by acid rain corrosion [1][2][3][4], industrial pollution [5,6], microbial erosion [7,8], and soluble salt crystallization [9]. Coating stone is an effective way to protect stone-built cultural relics from damage [10].…”
Section: Introductionmentioning
confidence: 99%
“…Mineral photocatalytic paints usually exhibit lower photocatalytic activity than the acrylic ones, but they have better stability during exposure to solar radiation 18 . For practical application of the photocatalytic paints it is important to determine the optimal thickness of the paint layer which is active under irradiation of light, because photocatalytic paint should be used only as an outer layer for coating.…”
mentioning
confidence: 99%